2008
DOI: 10.1001/archpediatrics.2007.8
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive Use by 15-Year-Old Students at Their Last Sexual Intercourse

Abstract: Setting: Data were collected in 2002 by self-report questionnaire from students in school classrooms.Participants: A cluster sample of 33 943 students aged 15 years from 24 countries.Main Outcome Measures: International standardized questions on ever having had sexual intercourse and contraceptive use at last sexual intercourse.Results: The percentages of students reporting having had sexual intercourse ranged from 14.1% in Croatia to 37.6% in England; 82.3% of those who were sexually active reported that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
2
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 25 publications
11
50
2
7
Order By: Relevance
“…43 Condom use is markedly lower among sexually active USA adults, where~20% overall 44,45 -and less than 50% of adults with multiple partners 44 -report use at last intercourse. Similarly discouraging patterns of condom use have been reported from general population surveys in other countries for both adolescents 46 and adults. 47 Likewise, Demographic Health Surveys (DHS) conducted in five subSaharan countries, where the HIV burden is high, suggest that condom use at last intercourse increased dramatically among men having higher-risk sex yet still remains only 40-70%.…”
Section: Consistent Usesupporting
confidence: 69%
“…43 Condom use is markedly lower among sexually active USA adults, where~20% overall 44,45 -and less than 50% of adults with multiple partners 44 -report use at last intercourse. Similarly discouraging patterns of condom use have been reported from general population surveys in other countries for both adolescents 46 and adults. 47 Likewise, Demographic Health Surveys (DHS) conducted in five subSaharan countries, where the HIV burden is high, suggest that condom use at last intercourse increased dramatically among men having higher-risk sex yet still remains only 40-70%.…”
Section: Consistent Usesupporting
confidence: 69%
“…Whereas European teens are not less likely to initiate sex during the high-school years compared with U.S. teens, they are much more likely to use contraception and to use more effective contraceptive methods (23,47). For example, 61% of 15-year-old females in the Netherlands in 2006/2007 report using the birth control pill at last sex, compared with just 11% of 15-year-olds in the United States (12,14).…”
Section: Yrbsmentioning
confidence: 99%
“…Poor communication with sexual partner in relation to contraception and not wanting to appear too knowledgeable or 'forward' have been linked with inconsistent or non-use of appropriate contraception 17,19 . Previous analyses of the 2001/02 HBSC survey 3 have found that a substantial minority of 15 year olds had engaged in sexual intercourse, and that condoms were the most frequent method of contraception at last intercourse reported by the sexually active respondents, followed by the dual use of condoms and contraceptive pills, and contraceptive pill only. Gaps in the knowledge base on adolescent sexual behaviour in relation to trends in contraception use 20 and comparable cross-national data 2 have previously been highlighted.…”
Section: Introductionmentioning
confidence: 96%
“…The challenges for maximising the sexual health of adolescents are substantial. Across industrialised nations, a relatively high proportion of those leaving compulsory education, at around age 16, have already experienced sexual intercourse, and have engaged in sexual risk behaviour 2,3 . Addressing the sexual health of young people by raising their commitment to safer sex has become a major issue among developed countries 1,2,4 .…”
Section: Introductionmentioning
confidence: 99%